Rethinking social transformation : - Giri, Ananta Kumar (Rawat Publications, 2001)
At the turn of the new century, we are confronted with an unprecedented challenge of rethinking the meaning and method of social transformation. This volume undertakes such a task and explores the implications of rethinking social transformation in various domains of our lives, viz. Education, politics, religion, spirituality, social movements and cultural criticism. Sixteen outstanding scholars from different vocations and disciplinary backgrounds have discussed different dimensions of contemporary transformations and have suggested new pathways of criticism and creativity. The book would be of interest not only to scholars of sociology, anthropology, philosophy, political science, history, literature, and cultural studies but also to activists in voluntary organizations and social movements. Contributors include Fred Dallmayr, Ramashray Roy, Amita Baviskar, K Raghavendra Rao, Vidya Das, Achyut Das, Ameena Mohsin, EC Sarangi, C. Sivakumar."